Neurological manifestations of immune origin after COVID-19 vaccination: retrospective case study - Granja López, Juan; Estebas Armas, Carlos; Lorenzo Dieguez, Manuel; Puertas Muñoz, Inmaculada; De Celis Ruiz, Elena; Rigual, Ricardo; Fernández-Fournier, Mireya; Torres Iglesias, Gabriel; Sánchez Velasco, Sara; Tallón Barranco, Antonio; Rogozina, Olga; Ramírez, Elena; et al. (Frontiers in Pharmacology, 2024)
Objectives: To know the frequency and characteristics of neurological manifestations of probable immune origin occurring after exposure to COVID-19 vaccination. In addition, to pre-study the usefulness of the Spanish pharmacovigilance system and lymphocyte transformation test in establishing causality. Methods: Retrospective case study, including patients admitted to the Neurology department from January 2021 to May 2022 with a probable neuroimmune disorder. Demographic, clinical and COVID19 vaccination antecedent data were collected from medical records. Results: From a total of 108 patients, 30 were excluded due to a different etiological diagnosis after follow-up. Thirty-six patients (46.2%) had received the COVID-19 vaccine in the previous 3 months (21.8% during the previous month). BioNTech-Pfizer vaccine was the most frequent in this group (63.9%). 69/108 were female and mean age 51.2 years (SD 22.59), with no significant difference with not recently-vaccinated (U-Mann Whitney,p=0.256). The neurological syndromes found were (vaccinated/total): polyradiculoneuropathy (8/16), encephalitis (5/11), multiple sclerosis relapse (5/16), optic neuritis (1/4), myelitis (3/6), cranial neuropathy (6/10), aseptic meningitis (1/3) and others (7/11). Acute immunosuppressive treatment was administered in 61.1% of cases and 47.2% presented complete clinical improvement, without significant differences with non-vaccinated patients (chi-square, p=0.570). Eleven vaccinated patients were studied in the pharmacovigilance office for possible adverse drug reaction. Causality according to the Spanish pharmacovigilance system (SPVS) algorithm was "Related" to COVID-19 vaccine (score ≥4) in 11 cases with positive in vitro study (lymphocyte transformation test) to polyethylene glycol-2000 and polysorbate-80 in 4 cases. Conclusions: Neuroimmune disorders appearing after administration of COVID-19 vaccine do not seem to present important differentiating clinical and/or evolutive features. Delayed hypersensitivity to vaccine excipients could be one of the pathophysiological mechanisms, and lymphocyte transformation test is a useful tool to identify it.